Involving patients in drug development for Neglected Tropical Diseases (NTDs): A qualitative study exploring and incorporating preferences of patients with cutaneous leishmaniasis into Target Product Profile development - Castro, María del Mar; Erber, Astrid C.; Arana, Byron; Cota, Gláucia; Denkinger, Claudia M.; Harrison, Nicole; Kutyi, Julia; López-Carvajal, Liliana; Plugge, Emma; Walochnik, Julia; Olliaro, Piero (PLOS Neglected Tropical Diseases, 2024)
Author summary Our study addresses the challenge of involving patients in defining which medical product would work for their condition. When designing a new medical product, it is customary to identify a “target product profile” (TPP), which identifies the characteristics the product should have to meet in order to address the medical need it is intended for. For the product to be used as intended and achieve the desired effects, it should be adapted to the conditions and the people who will use it, so, patients’ views are important, but rarely heard. Here, we use as an example cutaneous leishmaniasis, a skin and mucosal disease caused by a protozoan parasite, which disproportionally affects poor people across tropical and subtropical areas of the world. We collected patients’ views about product safety, efficacy, costs, treatment administration, and perceived barriers, that contribute to specifying product characteristics in the TPP. Overall, our study contributes to the limited body of knowledge with an example and an adaptable methodology to give patients a voice in designing adapted medical products. Patients input may also contribute to redefining aspects of a TPP, such as affordability, instead of just the cost per unit. The methodology used here can be adapted and used for other neglected diseases to give patients a voice in designing medical products.